Adoption of mobile fitness and dietary apps in India: an empirical study. (1st December 2020) - Sampat, Brinda; Prabhakar, Bala; Yajnik, Nilay; Sharma, Ashu
The use of mobile health (m-health) applications (apps) to provide healthcare services is on the rise in developing countries. However, their adoption in India is in its infancy. There is a rise in non-communicable diseases in India due to urbanisation, sedentary lifestyles and changing diets. Mobile fitness and dietary (MF&D) apps provide various features that can help promote healthy living. The purpose of this paper is to develop and empirically test a conceptual model by extending technology acceptance model (TAM) to establish how factors such as trust, social influence and perceived behavioural control influence the adoption of MF&D apps. A conceptual model with the hypothesised causal paths among the constructs have been empirically validated with the help of structural equation modelling (SEM) using AMOS with a sample of 234 MF&D app users. Results reveal perceived usefulness and trust are the most important factors that lead to adoption of MF&D apps.